Endovascular techniques in the treatment of acute mesenteric ischemia (review of literature) - G. A. Agasyan; A. B. Mironkov; A. D. Pryamikov; A. I. Khripun (Вестник хирургии имени И.И. Грекова)
The paper presents the latest data on applications of various types of endovascular interventions on the superior mesenteric artery. Efficiency of a number of devices for reperfusion therapy with acute mesenteric ischemia is described.The results of works with the largest samples of patients (frequency of laparotomy, intestinal resection and lethality), timing of endovascular surgery and comparative results of open and endovascular operations in the basin of the superior mesenteric artery are also discussed.